Structural Pluralism in Gerald Finzi’s Earth and Air and Rain - Natalie Burton (Janeway JS, 2020)
<span style="border: 1pt none windowtext; padding: 0cm; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">The genre of song cycle is complex and heterogeneous. As well as attracting significant contention in relation to matters of typology, the inherent aesthetic issues that arise from any intermedial union of words and music are compounded in the potential narrative consequences of the song cycle. Advocating melopoetic practices, my research seeks to examine the different cycle structures that emerge within the twentieth-century, English repertory. <span style="border: 1pt none windowtext; padding: 0cm; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Gerald Finzi’s Earth and Air and Rain, composed in 1936, has a somewhat ambiguous genesis and complex history in performance and publication. This article explores the work’s potential to be characterized by structural pluralism; that is, the possibility that there may be more than one way of understanding and navigating the cycle’s structure. <span style="mso-ascii-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: Calibri; color: black; border: none windowtext 1.0pt; mso-border-alt: none windowtext 0cm; padding: 0cm; background: white;">The genre of song cycle is complex and heterogeneous. As well as attracting significant contention in relation to matters of typology, the inherent aesthetic issues that arise from any intermedial union of words and music are compounded in the potential narrative consequences of the song cycle. Advocating melopoetic practices, my research seeks to examine the different cycle structures that emerge within the twentieth-century, English repertory. <span style="mso-ascii-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: Calibri; color: black; border: none windowtext 1.0pt; mso-border-alt: none windowtext 0cm; padding: 0cm; background: white;">Gerald Finzi’s Earth and Air and Rain, composed in 1936, has a somewhat ambiguous genesis and complex history in performance and publication. This article explores the work’s potential to be characterized by structural pluralism; that is, the possibility that there may be more than one way of understanding and navigating the cycle’s structure.
Keywords: Renaissance Literature; translation; Classical Studies; poetry; Ancient Rome